Mortality related to primary bariatric surgery in England. Issue 4 (26th October 2017) - Alam, M; Bhanderi, S; Matthews, J H; McNulty, D; Pagano, D; Small, P; Singhal, R; Welbourn, R
Abstract: Background: Bariatric surgery is an accepted treatment option for severe obesity. Previous analysis of the independently collected Hospital Episode Statistics (HES) data for outcomes after bariatric surgery demonstrated a 30-day postoperative mortality rate of 0·3 per cent in the English National Health Service (NHS). However, there have been no published mortality data for bariatric procedures performed since 2008. This study aimed to assess mortality related to bariatric surgery in England from 2009. Methods: HES data were used to identify all patients who had primary bariatric surgery from 2009 to 2016. Clinical codes were used selectively to identify all primary bariatric procedures but exclude revision or conversion procedures and operations for malignant or other benign disease. The primary outcome measures were HES in-hospital and Office for National Statistics (ONS) 30-day mortality after discharge. Results: A total of 41 241 primary bariatric procedures were carried out in the NHS between 2009 and 2016, with 29 in-hospital deaths (0·07 per cent). The 30-day mortality rate after discharge was 0·08 per cent (32 of 41 241). Both the in-hospital and 30-day mortality rates after discharge demonstrated a downward trend over the study period. Conclusion: Overall in-hospital and 30-day mortality rates remain very low after primary bariatric surgery. An increased uptake of bariatric surgery within the English NHS has been safe. Graphical Abstract: The present study assessed the mortality outcomes from primary bariatric surgery in England. The Hospital Episode Statistics (HES) database was used to identify patients who had bariatric surgery from 2009 to 2016, and the associated in-hospital and 30-day postdischarge mortalitites. Both the in-hospital and 30-day postdischarge mortality rates remained low and demonstrated a downwards trend, highlighting the low risk of bariatric surgery within the English National Health Service (NHS). Extremely safe surgery